CRYSTALLOGRAPHY EXPERT RECEIVES RESEARCH PRODUCTIVITY AWARD FOR SCIENTIFIC EXCELLENCE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, June 2015 – A world renowned Xray crystallographer and former Professor of Universiti Sains Malaysia (USM) School of Physics, Emeritus Professor Fun Hoong Kun once again brought glory to Malaysia when he was chosen as the recipient of the ‘Research Productivity Award: Health Sciences Category’ from King Saud University, Riyadh, Saudi Arabia.